Effect of Diphenyl Diselenide on Blood Glucose Level and Hepatic Indices in Alloxan Induced Diabetic Wistar Rats - Morayo, Ale Ebenezer; Umaru, Isaac John; Istifanus, Dafup Katdel (Darul Yasin Al Sys, 2024)
Diphenyl diselenide (DPDS) is an organoselenium compound that exhibits multi-pharmacological activities owing to its glutathione peroxidase (Gpx) mimicry. Herein, the effect of DPDS on blood sugar and hepatic indices in alloxan-induced diabetic wistar rats was investigated. Twenty albino rats were distributed into four groups: A was the normal control and recieved distilled water only, B was the negative control and recieved alloxan, C was the tested group and received alloxan with DPDS treatment, and D was the positive control and recieved alloxan with glibenclamide (standard andtidiabetic drug). Rats were induced with alloxan, and treated for 14 days. Animals weight and blood glucose level were measured, and on the last day, animals were sacrificed and blood was collected for the liver function analysis. Result revealed that alloxan administration led to a marked (p<0.05) fall in weights, but weight loss was reversed upon DPDS treatment. In addition, there was a profound (p<0.05) increase in blood glucose level of alloxan-treated rats. Nonetheless, treatment with DPDS exerted marked (P< 0.05) decrease in blood glucose level across day 7 and 14. Furthermore, the activities of serum hepatic enzymes, alkaline phosphatase (ALP), alanine transaminase (ALT), aspartate transaminase (AST) and γ-glutamyl transferase (GGT) were markedly (p<0.05) increased with concomitant reduction in the levels of total protein, albumin and globulin, but be that as it may, treatment with DPDS restored normalcy to the hepatic abnormalities and this effect was comparable to the standard drug. DPDS could therefore be suggested for future development of novel drug for diabetes and diabetes related complications.